The Impact of Financial Education and Socioeconomic Status on the Undergraduate Students' Financial Literacy - Khusaini Khusaini; Bambang Mardisentosa; Asep Ferry Bastian; Ruhiyat Taufik; Windi Widiawati (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2022)
Financial literacy is a crucial variable for researchers and policymakers because financial literacy's contribution encourages inhabitants to organize future financial planning and decision improvement. The study aims to empirically investigate the determinants of financial literacy such as financial education, parents' socioeconomic status, and gender. The authors used a cross-sectional survey approach with N = 325 samples. The result of measuring students' financial literacy showed a moderate condition (moderate level). The multiple linear regression models showed that parents' socioeconomic status significantly improved students' financial literacy. Meanwhile, financial education and gender did not prove significant in influencing students' financial literacy. The empirical study generated that encouraging parents is one of the essential policy elements in improving students' financial literacy. The higher students' socioeconomic status tends to encourage better financial planning and decision because they comprehend the literacy skills.